Farewell to the world a history of suicide - Barbagli, Marzio 1938- (Polity Press, 2015)
In this comparative study, sociologist Marzio Barbagli examines suicide as a socio-cultural, religious, and political phenomenon, exploring the reasons that underlie it and the meanings it has acquired in different cultures throughout the world. Drawing on a body of research carried out by historians, anthropologists, sociologist, political scientists, and psychologists, Barbagli argues that a satisfactory theory of suicide cannot limit itself to the two causes highlighted by French sociologist Émile Durkheim--namely, social integration and regulation--but must rather provide a new account that links the motives for and significance attributed to individual actions with the people for and against whom individuals take their lives.--From publisher description.